Increase Tourism Attraction in Kota Lama Semarang: Potential Aspect and Development Strategy - Aulia, Wahyu Mafatikhul; Rosyid, Azis Nur; Mukti, Artin Bayu (Sekolah Vokasi, Universitas Gadjah Mada, 2023)
Semarang Old City is a Dutch heritage city with a European style architecture and a historical part of Semarang city. Experiencing a decline in the value of city functions is caused: Lack of government attention, ownership status, switching of building functions, and natural factors. Kota Lama has the potential to be a tourist destination, it takes a strategy of amenities development and marketing. This research aims to find out the potential of The Old City as a tourist destination, development strategies to be carried out as well as preservation efforts. This research was conducted by qualitative method conducted in the old City area. Data collection techniques are carried out with observation, interview and document study. Based on the results of data collection can be concluded that: (1) Kota Lama is very potentially a heritage tourism destination, (2) it needs a strategy of development of amenities and marketing, (3) Preservation efforts are carried out, thus becoming a tourist attraction that impacts on social, economic and environmental life.